USE OF MULTIMEDIA TECHNOLOGIES IN THE CONDITIONS OF DISTANCE EDUCATION - Radchenko, Marina (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article defines the essence and components of distance learning, establishes the place of multimedia technologies in the basic model of distance education. The results of a comparative study of the impact of multimedia tools on the cognitive sphere of students studying offline and online are given. A list of criteria for analyzing the quality of a multimedia presentation is offered. Prospects for further research in the direction of using multimedia technologies in the conditions of distance learning are outlined.